Фізико-хімічні й термодинамічні основи синтезу мінералів та їх гідратації й дегідратації для отримання штучного каменю з заданими властивостями - Пушкарьова, Катерина Костянтинівна; Шабанова, Галина Миколаївна (Український державний університет залізничного транспорту, 2015)
Встановлені нові фізико-хімічні закономірності синтезу, гідратації та дегідратації мінералів та їх склоподібних аналогів для отримання штучного каменю з заданими властивостями, у т.ч. високоміцного, жаростійкого. Сформульовані основні принципи його композиційної побудови, які дозволяють завдяки регулюванню фазового складу продуктів твердіння здійснити направлений синтез штучного каменю з прогнозованими термомеханічними характеристиками. Теоретично обґрунтовано можливість створення нового класу барійвмісних цементів поліфункціонального призначення, що базується на прогнозуванні необхідних комбінацій фаз з урахуванням законів термодинаміки в прикладному застосуванні до фазових рівноваг багатокомпонентних барійвмісних оксидних систем. Встановлено, що основними продуктами їх гідратації є гідроалюмінати, гідросилікати та гідроферити у кристалічному, криптокристалічному або аморфному станах, які в процесі твердіння утворюють високоміцний конгломерат.

Installed new physical and chemical laws of synthesis, hydration and dehydration of minerals and glassy analogous for artificial stone with predetermined properties. It is shown that the optimal conditions for the synthesis strength of artificial stone created at forming a gel phase as a part of hydration products. A new approach to assessing the quality of artificial stone structure that takes into account the degree of crystal-chemical similarity for new products hydration at different stages of structures formation stone in a wide temperature range. Its proposed criterion of similarity crystal products hydration and dehydration that allowed to quantify the changing state of the stone structures at the elevated temperature. Based on the developed ideas about the physical and chemical processes of hydration and dehydration of mineral binders formulated the basic principles of artificial stone composite construction with given properties, including high-strength, heat-resistant, which allows by adjusting the phase of hardening products implement directed synthesis of artificial stone predictable thermomechanical characteristics. Theoretically proved the possibility of creating a new class of multifunctional purpose bariumcontent cements based on the prediction of the required combinations of phases, taking into account the laws of thermodynamics as applied to the use of phase equilibria of multicomponent systems. The features of the processes of hydration and hardening cements of bariumcontent new class and found that the main products of hydration are hidroaluminates, hydrosilicates and hydroferrous crystalline, criptocrystalline or amorphous states. Its phases take part in forming of structure high strength conglomerate.
Physico-chemical and thermodynamic fundamentals of synthesis of minerals and their hydration and dehydration to produce artificial stone with given properties
Keywords: міцність; продукти твердіння; подібність кристалохімічна; цемент барійвмісний; strength; cristal-chemical similarity; hardening products; bariumcontent cements